2022
DOI: 10.5114/wiitm.2022.113567
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term outcomes as well as anal function of transanal natural orifice specimen extraction surgery versus conventional laparoscopic surgery for sigmoid colon or rectal cancer resection: a retrospective study with over 5-year follow-up.

Abstract: Introduction:To date, long-term safety including functional outcomes of transanal natural orifice specimen extraction surgery (NOSES) for colorectal cancer resection has not been confirmed. Aim: To explore the short-and long-term outcomes as well as anal function of transanal NOSES versus conventional laparoscopic surgery for sigmoid colon or rectal cancer resection. Material and methods: A retrospective review of data from a prospectively maintained database was performed to analyze the data of 69 patients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…It can be assumed that even though the tumor cell test result is positive, it does not affect the long-term outcome of patients in the NOSE group, and the 2-year disease-free survival rate after surgery is at least comparable to that of conventional surgery. This is in line with the findings of existing studies [ 9 , 13 , 20 ]. In 2019, Liu et al also demonstrated through a meta-analysis that NOSE for colorectal cancer can achieve satisfactory oncological outcomes [ 21 ].…”
Section: Discussionsupporting
confidence: 93%
“…It can be assumed that even though the tumor cell test result is positive, it does not affect the long-term outcome of patients in the NOSE group, and the 2-year disease-free survival rate after surgery is at least comparable to that of conventional surgery. This is in line with the findings of existing studies [ 9 , 13 , 20 ]. In 2019, Liu et al also demonstrated through a meta-analysis that NOSE for colorectal cancer can achieve satisfactory oncological outcomes [ 21 ].…”
Section: Discussionsupporting
confidence: 93%
“…Faster postoperative recovery also reduced the cost of surgery and significantly reduced the economic burden for gastric cancer patients. This result of rapid recovery is also seen in NOSES group patients with sigmoid colon cancer or rectal cancer resection [13]. Meanwhile, similar results from faster postoperative recovery were observed when we included case reports.…”
Section: Discussionsupporting
confidence: 83%
“…Natural orifice specimen extraction was a surgical method that aimed to reduce surgical trauma by removing the need for an incision into the abdominal wall [ 24 ]. The incision to extract the specimen was usually made in the rectum [ 13 ], vagina or mouth. Although the NOSES-related reports were limited in gastrectomy, the use of NOSES in both EGC and AGC had been confirmed to be feasible and safe [ 8 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations